Pengaruh Sikap, Kontrol Perilaku, dan Literasi Keuangan Terhadap Niat Berinvestasi Saham Syariah Pada Masyarakat Kota Pekanbaru - Nisaa, Khairun; H, Herlinda; J, Julina (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the influence of attitudes, behavioral control and financial literacy on the intention to invest in Sharia shares among the people of Pekanbaru city. The population of this research is people who are interested in investing in Sharia shares in the city of Pekanbaru. The total research sample was 100 people using the incidental sampling method and using the Cochran formula. Analysis of research data is quantitative using multiple linear regression methods. The research results show that there is an influence of attitude, behavioral control, and financial literacy on the intention to invest in Sharia shares. This is proven by the value Fcount (228.637) > Ftable (2.70) with Sig. (0.000) < 0.05. The coefficient of determination obtained was 0.737 or 73.7% for Sharia Stock Investment Intentions, and the remaining 26.3% was influenced by other variables not examined in this research.